Active emotions and personal growth initiative fuel employees' daily job crafting: A multilevel study - Yannick Griep; Els Vanbelle; Anja Van den Broeck; Hans De Witte (BRQ Business Research Quarterly, 2022)
In this study, we expand on the existing work on job crafting by focusing on (1) within-person fluctuation in affective experiences in relation to job crafting and person-job fit and (2) between-person fluctuations in personal growth initiative (PGI) as an important boundary condition of these relationships. Using multilevel data from 116 employees (341 observations), our results showed that fluctuations in positive active emotions (PAE) and negative active emotions (NAE) related positively to daily job crafting; this relationship was moderated by overall PGI levels. Next, we found a positive association between daily job crafting and daily person-job fit. Finally, we found indirect effects from NAE and PGI to daily fluctuations in person-job fit via daily fluctuations in job crafting; NAE and PGI energized employees to engage in daily job crafting, which contributed to their daily person-job alignment. We discuss implications for theory and practice.
Keywords: M0; 650; Active emotions; job crafting; multilevel; person-job fit; personal growth initiative